2021
DOI: 10.5009/gnl20289
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Long-term Prognosis of Elderly-Onset Ulcerative Colitis in a Population-Based Cohort in the Songpa-Kangdong District of Seoul, Korea

Abstract: Background/Aims We aimed to evaluate the clinical characteristics and long-term prognosis of elderly-onset ulcerative colitis (EOUC) in Korean patients over a 30-year period using a well-established population-based cohort in the Songpa-Kangdong district of Seoul, Korea. Methods Clinical characteristics and prognosis were compared between two groups EOUC, defined as UC diagnosed in individuals aged ≥60 years and non-EOUC (N-EOUC), defined as UC diagnosed in individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Concerning disease extension at diagnosis (Table 1 ), in a meta-analysis from 2016, left-sided colitis prevails in older-onset disease [ 14 ]. This finding was confirmed by subsequent studies [ 4 , 15 17 ], whereas in other studies, extensive colitis [ 18 ] or proctitis [ 19 , 20 ] were more frequent in late-onset UC. Some studies found significant differences for disease extension at diagnosis between adult- versus late-onset UC [ 3 , 4 , 6 , 8 , 9 , 16 , 17 , 21 , 22 ], whereas others did not find such differences [ 15 , 18 20 ].…”
Section: Presentation and Disease Coursesupporting
confidence: 67%
See 1 more Smart Citation
“…Concerning disease extension at diagnosis (Table 1 ), in a meta-analysis from 2016, left-sided colitis prevails in older-onset disease [ 14 ]. This finding was confirmed by subsequent studies [ 4 , 15 17 ], whereas in other studies, extensive colitis [ 18 ] or proctitis [ 19 , 20 ] were more frequent in late-onset UC. Some studies found significant differences for disease extension at diagnosis between adult- versus late-onset UC [ 3 , 4 , 6 , 8 , 9 , 16 , 17 , 21 , 22 ], whereas others did not find such differences [ 15 , 18 20 ].…”
Section: Presentation and Disease Coursesupporting
confidence: 67%
“…Severity of disease at onset seems to be similar between adult- and late-onset UC [ 20 , 22 ] with similar steroid needs at onset [ 3 , 14 16 ]; in a former report, a more protracted first episode was found together with a shorter duration of remission compared with young adult-onset disease [ 23 ].…”
Section: Presentation and Disease Coursementioning
confidence: 99%
“…There are many reports that the hospitalization rate of elderly UC patients is significantly higher than that of non‐elderly UC patients 12,19,20 . In an accompanying article by Moroi et al (a Nationwide Study from Japan), the rate of in‐hospital death of elderly patients is higher 21 .…”
Section: Clinical Presentation In Elderly Ulcerative Colitismentioning
confidence: 99%
“…There are many reports that the hospitalization rate of elderly UC patients is significantly higher than that of non‐elderly UC patients. 12 , 19 , 20 In an accompanying article by Moroi et al (a Nationwide Study from Japan), the rate of in‐hospital death of elderly patients is higher. 21 One of the reasons of worse outcomes is that older‐onset UC patients have less chances of receiving strong immunosuppressive therapies considering the comorbidities and adverse events such as infections.…”
Section: Clinical Presentation In Elderly Ulcerative Colitismentioning
confidence: 99%
“…In the current issue, Park et al 9 reported data comparing clinical characteristics and long-term disease course of EOUC with those of non-EOUC in a well-established population-based cohort in Korea. This cohort study included 99 patients with EOUC and 866 patients with non-EOUC between 1986 and 2015.…”
mentioning
confidence: 99%